Dual Contrary Personalities Of Dr.Hannibal Lecter Reflected The Silence Of The Lambs Novel (1988): A Psychoanalytic Approach - Brosnan, Fachrur, Drs. Abdillah Nugroho, M. Hum, Dr. Anam Sutopo, M.Hum (2014)
The major problem in this study is to show person with dual contrary personality reflected Thomas Harris The Silence of the Lambs novel by using psychoanalytic approach. It is conducted by analyzing the novel based on its structural elements and based on psychoanalytic criticism. This research is qualitative research. Type of data of the study is text and image taken from two data sources: primary and secondary. The primary data source is The Silence of the Lambs novel written by Thomas Harris released in 1988. While the secondary data sources are taken from the books of literary, internet, and other relevant information. Both data are collected through library research and analyzed by descriptive analysis. Using a psychoanalytic criticism as the theoretical framework, the research shows the following findings. First, based on structural analysis of this novel, it is clear for the researcher to conclude that the literary elements of The Silence of the Lambs form a unity in which one element supports the others and the whole elements reflect the theme of the novel. Thomas Harris has proven by delivering a message through its theme that the unnatural obsession can cause negative ability in this novel. Second, based on psychoanalytic analysis, Thomas Harris wants to convey the psychological phenomena that type of personality.